Utilization of porang tuber starch enriched with ginger extract as an edible coating for avocado (Persea americana Mill.) storage [Pemanfaatan pati umbi porang diperkaya ekstrak jahe sebagai edible coating untuk penyimpanan buah alpukat (Persea americana Mill.)] - Sabahannur, Siti; Ralle, Andi; Faiz, Muhammad (Jurnal Teknologi & Industri Hasil Pertanian, 2025)
Avocado is a climacteric fruit that experiences a surge in respiration and ethylene production after harvest, which accelerates its deterioration. One method to extend its shelf-life post-harvest is using edible coatings. This study evaluated the effects of various concentrations of edible coatings made from porang tuber starch and ginger extract on avocado quality during storage. A two-factor experiment was arranged in a randomized block design with 3 replications.  The two factors studied were the concentrations of porang starch (0%, 1.5%, 2%, and 2.5%) and the concentrations of ginger extract (0%, 4%, 6%, and 8%). Observed parameters included weight loss, total soluble solids, firmness, damage percentage, and sensory color, texture, and taste evaluations. Storage was conducted at room temperature (27±2°C) for 10 days. The research results indicated that the quality of avocados was significantly affected by the single treatment using edible coatings made from porang starch or ginger extract, while the interaction between the two only had a significant effect on weight loss. The use of 2% porang starch or 6% ginger extract was able to reduce weight loss by up to 13.73%, maintain fruit firmness at 7.71±1.383 kgf.cm⁻², total soluble solids at 1.25±0.127 °Brix, and resulted in sensory scores of color 1.67±0.608 (purple), texture 1.58±0.568 (soft), and taste 2.25±0.688 (slightly liked). The damage rate of the avocados reached 47.21±16.665%. Thus, this combination of edible coating proved effective in maintaining the physical, chemical, and sensory quality of avocados during storage.